2021
DOI: 10.3390/fuels2030016
|View full text |Cite
|
Sign up to set email alerts
|

Process Simulation Modelling of the Catalytic Hydrodeoxygenation of 4-Propylguaiacol in Microreactors

Abstract: A process simulation model was created using Aspen Plus to investigate the hydrodeoxygenation of 4-propylguaiacol, a model component in lignin-derived pyrolysis oil, over a presulphided NiMo/Al2O3 solid catalyst. Process simulation modelling methods were used to develop the pseudo-homogeneous packed bed microreactor. The reaction was conducted at 400 °C and an operating pressure of 300 psig with a 4-propylguaiacol liquid flow rate of 0.03 mL·min−1 and a hydrogen gas flow rate of 0.09 mL·min−1. Various operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The decomposition of formic acid reaction was modelled using the software Aspen Plus V11. The model selected to accurately predict the behaviour of the vapour-liquid equilibrium of the reaction system was the non-random two-liquid (NRTL) model [44]. The process-modelling studies were performed in a batch reactor with a 100 mL volume and a temperature range of 30-60 • C. Characteristically, 10 mL of the required concentration of formic acid was deposited into the batch reactor.…”
Section: Modelling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of formic acid reaction was modelled using the software Aspen Plus V11. The model selected to accurately predict the behaviour of the vapour-liquid equilibrium of the reaction system was the non-random two-liquid (NRTL) model [44]. The process-modelling studies were performed in a batch reactor with a 100 mL volume and a temperature range of 30-60 • C. Characteristically, 10 mL of the required concentration of formic acid was deposited into the batch reactor.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…We utilised the capabilities of Aspen Plus to develop a simple innovative reaction system by integrating the phase-equilibrium exercises. It has been observed that both CFD and process-simulation modelling have the ability to predict different reactions with similar results [44]. The production of H 2 from the decomposition of formic acid has been investigated using a 2%Pd 6 Zn 4 catalyst in a batch reactor.…”
Section: Introductionmentioning
confidence: 99%